(untitled) (Cambridge, 2002)
This is a book about laser cooling, a new research field with many potential applications. The authors present an original approach, using the tools and concepts of statistical physics. A new understanding of laser cooling, both intuitive and quantitative, is obtained. The volume also comprises a case study allowing non-Gaussian (Lévy) statistics, a technique being used more frequently in many different fields.
Keywords: Laser manipulation (Nuclear physics),Laser cooling,Atoms,Thao tác tia Laser ( vật lý hạt nhân ),Làm nguội Laser,Nguyên tử; Cooling,Làm mát